2017
DOI: 10.1016/j.neuron.2017.09.058
|View full text |Cite
|
Sign up to set email alerts
|

“Silent” NMDA Synapses Enhance Motion Sensitivity in a Mature Retinal Circuit

Abstract: Summary Retinal direction-selective ganglion cells (DSGCs) have the remarkable ability to encode motion over a wide range of contrasts, relying on well-coordinated excitation and inhibition (E/I). E/I is orchestrated by a diverse set of glutamatergic bipolar cells that drive DSGCs directly, as well as indirectly through feed-forward GABAergic/cholinergic signals mediated by starburst amacrine cells. Determining how direction-selective responses are generated across varied stimulus conditions requires understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 66 publications
(127 reference statements)
0
30
1
Order By: Relevance
“…), probably via NMDA receptors to ensure robust direction computation (Sethuramanujam et al . ). BP(3/4)‐II provides exclusive excitation to DSGCs via AMPA receptors and possibly via NMDA receptors.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…), probably via NMDA receptors to ensure robust direction computation (Sethuramanujam et al . ). BP(3/4)‐II provides exclusive excitation to DSGCs via AMPA receptors and possibly via NMDA receptors.…”
Section: Discussionmentioning
confidence: 97%
“…By contrast, recent studies examining DSGCs in mouse and rabbit retina have suggested that under conditions of low stimulus contrast, ACh can be the primary source of excitation (Sethuramanujam et al 2016;Brombas et al 2017). Under low contrast conditions, a common set of high sensitivity bipolar cells appear to drive starbursts via AMPA receptors and DSGCs via NMDA receptor-dominated synapses (Sethuramanujam et al 2017). As NMDA receptors alone are unable to strongly depolarize ganglion cells, bipolar cell inputs to ganglion cells remain silent in the absence of cholinergic excitation (Sethuramanujam et al 2016).…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations